2021
DOI: 10.3390/biom11020233
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites, Ferulic Acid and p-Hydroxybenzoic Acid Induced Toxic Effects on Photosynthetic Process in Rumex acetosa L.

Abstract: The elimination of broadleaf weeds from agricultural fields has become an urgent task in plant and environment protection. Allelopathic control is considered a potential approach because of its exclusive and ecological safety measures. Plant secondary metabolites also called allelochemicals are released from plant leaves, roots, stem, bark, flowers and play significant roles in soil rhizosphere signaling, chemical ecology, and plant defense. The present study was carried out to evaluate the impact of two allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…This is in agreement with published data reporting that higher SA concentrations (1.0 mM) have an inhibitory effect on photosynthesis and overall growth performance in B. juncea cultivars [34]. Moreover, a high concentration of FA (1.5 mM) inhibited photosynthesis and can be used as a bioherbicide [35].…”
Section: Fa and Sa Treatments Stabilize Photosynthetic Parameters Under Salinity Stresssupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with published data reporting that higher SA concentrations (1.0 mM) have an inhibitory effect on photosynthesis and overall growth performance in B. juncea cultivars [34]. Moreover, a high concentration of FA (1.5 mM) inhibited photosynthesis and can be used as a bioherbicide [35].…”
Section: Fa and Sa Treatments Stabilize Photosynthetic Parameters Under Salinity Stresssupporting
confidence: 92%
“…To our knowledge, the effect of FA on the photosynthetic apparatus has not been studied to date. In a recent publication, it was shown that a high concentration of FA (1.5 mM) inhibits photosynthesis and can be used as a bioherbicide [35], although there are no reports on the effects of lower concentrations of FA on the photosynthetic apparatus. However, it has been shown that plants with higher levels of endogenous FA showed better photosynthetic performance under stress conditions [40].…”
Section: Fa and Sa Treatments Stabilize Photosynthetic Parameters Under Salinity Stressmentioning
confidence: 99%
“…Allelochemicals exert their phytotoxic effects through different pathways, and the biological activity on the target weeds also varies from one weed to another 5,43,65 . Allelochemicals can be considered an important part of ecological weed management, but it is necessary to understand the class of allelochemicals and their possible mechanisms of action 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Ferulic and p-hydroxybenzoic acids Inhibition of photosynthetic attributes Rumex acetosa [36] Ferulic and p-hydroxybenzoic acids…”
Section: Mechanisms Target Species Referencesmentioning
confidence: 99%
“…The mode of action of natural products includes multiple mechanisms, such as the reduction in percent and rate of germination together with reductions in root and shoot growth [ 33 , 34 ], interference with photosystem-II through electron transport [ 12 ], [ 35 , 36 ] and primary action on ATP production. In addition, this includes the inhibition of chloroplast oxygen evolution, a strong effect on mitochondrial function, alteration of nutrient absorption, chlorophyll pigments, carbon isotope discrimination [ 11 , 12 ], or water use efficiency [ 12 , 37 ].…”
Section: Introductionmentioning
confidence: 99%